IT STRATEGIES OF SMALL AND MEDIUM-SIZED ENTERPRISES IN THE ERA OF DIGITAL TRANSFORMATION - Ziyoda Rustamova (Ecominds Press, 2025)
Digital transformation has become an integral part of the modern economy, demanding substantial changes across all sectors, particularly in the operations of small and medium-sized enterprises (SMEs). This article explores the importance of developing and implementing effective IT strategies for SMEs in the digital age. Through IT strategies, businesses can maintain competitiveness, integrate innovations, enhance customer engagement, and ensure digital security. The study analyzes the impact of implementing digital technologies such as cloud computing, artificial intelligence, data analytics, and automation on SMEs. It also discusses the common challenges encountered while formulating IT strategies and proposes practical solutions. The article provides actionable recommendations for SME leaders, researchers, and IT professionals seeking to adapt to digital transformation.
Keywords: Digital transformation, IT strategy, small business, medium business, digital technologies, innovation, cloud computing, artificial intelligence, automation, data analytics, cybersecurity, SMEs.